Neuroleptic malignant syndrome in a patient with bipolar depression on stable dose of quetiapine - Zakaria, Rozanizam; Husain, Maruzairi; Chin, Lie Joo (Ministry of Health Brunei Darussalam, 2016)
We report a case of a 37-year-old widow with a diagnosis of bipolar I disorder who presented with catatonia and neuroleptic malignant syndrome (NMS) while in the depressive phase of her illness. The neuroleptic malignant syndrome developed in the context of a stable dose of long-acting quetiapine (300mg) for five years. Her depression and catatonic state were hypothesised as the contributing factors for her NMS. Her catatonic symptoms were initially managed with regular benzodiazepines and she was later given electroconvulsive therapy during her admission. Her NMS improved after five days and her catatonic symptoms fully resolved after the second electroconvulsive therapy. The aim of this case report is to highlight the presentation of NMS in a depressed and catatonic patient, despite her long-term stability and a relatively low dose of quetiapine.